PENGARUH GAYA KEPEMIMPINAN DAN STRES KERJA TERHADAP KINERJA PEGAWAI (STUDI KASUS DINAS KESEHATAN KABUPATEN JEMBER) - Diansyah, Riski Nurrachman (BISMA: Jurnal Bisnis dan Manajemen, 2016)
Abstract : This study aims to identify and analyze the influence of leadership style and job stress on employee performance Jember District Health Office as well as the differences in the performance of employees to staff a male or female and the difference in employee performance against employees with civil servant status or Honorary. This study was designed with the explanatory survey method. The number of samples in this study a total of 100 employees in Jember District Health Office. The data were analyzed using multiple linear regression analysis. Leadership Styles analysis showed a significant effect on employee performance Jember District Health Office. Job Stress significant effect on employee performance Jember District Health Office. Leadership Style and Job Stress significant effect on employee performance Jember District Health Office. There are differences in performance of civil servants employees higher than the performance of employees Honorary Jember District Health Office. There are differences in performance female employees is higher than the performance of employees male - male Jember District Health Office.Keywords: Leadership Style, Job Stress, Performance, HR